Predictive value of serum uric acid in hospitalized adolescents and adults with acute asthma - Abdulnaby NK; Sayed AO; Shalaby NM (Dove Medical Press, 2016)
Nasser Keshar Abdulnaby,1 Ashraf Othman Sayed,2 Nehad Mohamed Shalaby3 1Chest Diseases and Tuberculosis Department, Faculty of Medicine, Cairo University, Cairo, 2Department of Pediatrics, Children and Women’s University Hospital, Minia University, El-Minya, 3Department of Pediatrics, Mansoura University Children’s Hospital, Faculty of Medicine, Mansoura University, Mansoura, Egypt Background: High serum uric acid (sUA) is an indicator of oxidative stress and is linked to tissue hypoxia in asthma. The objective of this case series was to investigate the prognostic role of sUA in patients with acute asthma exacerbations and the link between sUA and spirometric lung tests. Patients and methods: This cross-sectional observational study included 120 patients with acute asthma exacerbations and 120 controls, categorized according to peak expiratory flow rate into moderate, and severe and life-threatening asthma. On admission, a detailed history was obtained and investigations were carried out regarding oxygen saturation (SaO2), arterial blood gas, spirometry, sUA, number of asthma exacerbations, smoking status, history of previous hospitalization, intensive care unit admission, and mechanical ventilation. Results: The current study revealed higher sUA in asthmatic patients compared with healthy subjects and in severe asthma patients compared with moderate asthma patients (P<0.001). A positive correlation of sUA with asthma severity, number of asthma exacerbations and smoking index (r=0.6, 0.42 and 0.29, respectively, P<0.001) and a negative correlation of sUA with SaO2, partial pressure of arterial oxygen (PaO2), percent predicted forced vital capacity, percent predicted forced expiratory volume (FEV%) and peak expiratory flow rate percent of predicted (PEFR%; r=-0.48, -0.29, -0.44, -0.44 and -0.66, respectively, P<0.001) were observed. Degree of asthma severity, number of asthma exacerbations, and smoking index were significant predictors of high sUA (R2=0.43, P<0.001) in multiple linear regression model 1. SaO2 and PEFR% were significant predictors of high uric acid (R2=0.50, P<0.001) in model 2. The sensitivity and specificity of sUA in predicting severity of asthma at the cutoff point of 6.3 mg/dL were 80% and 90%, respectively. The odds ratios of sUA, number of asthma exacerbations, and asthma duration were 5.4, 1.95 and 1.3, respectively. Conclusion: sUA may be a useful marker of predictive value of severity of asthma exacerbations. Keywords: asthma, uric acid, exacerbation, spirometery